PENYIDIKAN TINDAK PIDANA KORUPSI DALAM SISTEM PENEGAKAN HUKUM DI INDONESIA (Studi di Kepolisian Daerah Kepulauan Riau) - Ahmad Ramadhan (Fakultas Hukum Universitas Muhammadiyah Palu, 2017)
This research is to analyze the authority of Police of Kepri in Corruption Crime Investigation. Method of approach used is normative juridical research that is analyze the law in writing, literature and document study used as the main material. Field data was obtained through structured interviews that were used as supporting data / auxiliaries to police officers / investigators at Polda Kepri, Barelang Police and Tanjungpinang Police. This research was conducted at the Riau Islands Regional Police especially the Special Criminal Investigation Directorate of Riau Islands Police, Barelang Police and Tanjungpinang Police. The results of the study found that the investigation of corruption in Polda Kepri was carried out in accordance with the authority possessed by Polri investigators. The investigation of criminal acts of corruption, in addition to prove the perpetrators' actions, also to the maximum extent possible to restore the state financial losses. In its implementation, corruption criminal investigation is influenced by legal factors, law enforcement factors, facilities or facilities supporting law enforcers, community factors, and) cultural